Mike Meyers' certification passport CompTIA A+ certification exams 220-901 & 220-902 - Meyers, Mike 1961-; Jernigan, Scott; Everett, Travis A. (McGraw-Hill Education, 2016)
Mike Meyers' bestselling quick review guide - revised to cover the 2012 CompTIA A+ exams Written by the most trusted name in CompTIA A+ training and exam preparation. This edition focuses on only what you need to know to pass the tests, and the unique travel theme helps you remember key concepts.
Includes index. - Includes bibliographical references and index. - Online resource; title from title page (viewed September 7, 2016)
Keywords: Computing Technology Industry Association -- Study guides -- Examinations; Electronic data processing personnel -- Certification; Computer technicians -- Study guides -- Certification; Microcomputers -- Study guides -- Maintenance and repair -- Examinations; Computing Technology Industry Association; Micro-ordinateurs; Entretien et réparations; Examens; Guides de l'étudiant; Computer technicians; Certification; Electronic data processing personnel; Certification; Examinations; Microcomputers; Maintenance and repair; Examinations; examination study guides; Study guides; Guides de l'étudiant